Chemical composition of a palomar 12 blue straggler. Issue 4 (26th March 2022) - Pasquini, L; Bonifacio, P; Pulone, L; Modigliani, A; Brocato, E; Sbordone, L; Randich, S; Cupani, G
ABSTRACT: With the equivalent area of a 16-m telescope, ESPRESSO in 4UT mode allows to inaugurate high resolution spectroscopy for solar-type stars belonging to extragalactic globular clusters. We determine the chemical composition of an extragalactic blue straggler (BS). The star has a G magnitude of 19.01 and belongs to the globular cluster Pal12, that is associated to the Sagittarius dwarf galaxy. Abundances are computed by using high resolution spectroscopy and LTE analysis. Two 50 min ESPRESSO spectra, co-added, provide a signal-to-noise ratio of ∼25 with a resolving power R∼70 000. This allows us to measure with good precision abundance of several (13) elements. Li could help to distinguish between formation models of BS; we are able to set a 3σ upper limit of Li = 3.1, which is still too high to discriminate between competing models. The abundances we retrieve for the BS are compatible with those of giant stars of Pal 12 published in literature, re-analysed by us using the same procedure and line list. Small differences are present that can be ascribed to NLTE effects, but for Mg the BS shows a large under-abundance. The most likely explanation is that the BS atmosphere is dominated by gas processed through the Mg-Al cycle, but we have no suitable Al or Na lines to confirm this hypothesis. We show that ESPRESSO with 4UT can be used to derive precise abundances for solar-type stars fainter than magnitude 19. At these magnitudes a proper sky subtraction is needed and in crowded field the targets must be chosen with utmost care, to avoid contamination of the sky fibre from nearby stars.